Calculation of Effective Emissivity of Isothermal Diffuse Cylindrical-inner-cone Cavity using Polynomial Interpolation Technique - Tuan, Ta Van; Minh, Nguyen Quang (Communications in Physics, 2017)
A precise calculation of the effective emissivity of isothermal diffuse cylindrical-inner-cone cavities is presented using the polynomial interpolation technique. Particularly, results are obtained for the effective emissivity of conical bases of the isothermal diffuse cylindrical-inner-cone cavities. Comparisons are made between Chu Zaixiang’s and our results for various values of the axial length, the radius of aperture in the lid and the half-angle of the inner cone. These demonstrate considerable simplicity and high accuracy of the calculating technique can be achieved, especially for the cavities of high intrinsic emissivity of the wall, long cylinder length, and small aperture radius. For application, a series of explicit analytical expressions in the polynomial forms are also presented.